2015
DOI: 10.1177/0885328215592854
|View full text |Cite
|
Sign up to set email alerts
|

Treatment study of distal femur for parathyroid hormone (1–34) and β-tricalcium phosphate on bone formation in critical size defects in rats

Abstract: The objective of this study was to evaluate local bone formation following systemic administration of parathyroid hormone (1-34), a surgically implanted synthetic β-tricalcium phosphate bone biomaterial serving as a matrix to support new bone formation. Twelve weeks after bilateral ovariectomy, all rats underwent bone defect in the distal femurs, and β-tricalcium phosphate was implanted into critical sized defects. After defect operation, all animals were randomly divided into four groups and received followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…32 Several previous studies have investigated the influence of osteoporosis on bone healing using OVX rats as an experimental model; this is a well-studied method that simulates the changes in postmenopausal women, and needs an average of three months for the osteopenic condition to onset. 30,3335 As expected, OVX resulted in a significant decrease in the femoral metaphysic BMD after three months. Femoral metaphysis was chosen as the implant site because in OVX rats, cancellous bone mass in the metaphyseal region of long bones is rapidly reduced and it is large enough in rats to allow implantation, which indicated that this was a suitable condition as a model of osteoporosis.…”
Section: Discussionsupporting
confidence: 73%
“…32 Several previous studies have investigated the influence of osteoporosis on bone healing using OVX rats as an experimental model; this is a well-studied method that simulates the changes in postmenopausal women, and needs an average of three months for the osteopenic condition to onset. 30,3335 As expected, OVX resulted in a significant decrease in the femoral metaphysic BMD after three months. Femoral metaphysis was chosen as the implant site because in OVX rats, cancellous bone mass in the metaphyseal region of long bones is rapidly reduced and it is large enough in rats to allow implantation, which indicated that this was a suitable condition as a model of osteoporosis.…”
Section: Discussionsupporting
confidence: 73%
“…In the experiments conducted, OVX rat was used as an animal model. 22,23 In 3-month-old rats, the effect of OVX on their skeletons was manifested in 12 weeks or less, and the characteristics of the bone loss are mostly similar to those in an aged rat model. Also, in the present experiment, a remarkable decrease in trabecular bone volume was histologically noted in the distal femur of rats at 12 weeks after OVX, which indicated that this was a suitable condition as a model of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-five rats were subject to bilateral ovariectomization (OVX), and the surgical procedures were reported in our previous studies. 22,23 Twelve weeks after bilateral ovariectomy ( N = 45) or Sham operation ( N = 5), 5 OVX rats were randomly selected and the 5 sham-operated ones were euthanized. The distal femurs were harvested for bone mineral density (BMD), micro-computed tomography (micro-CT), and histological evaluation to confirm the establishment of osteoporosis.…”
Section: Methodsmentioning
confidence: 99%
“…Once the successful establishment of the depression model was confirmed by behavior evaluation, 10 rats from each group was collected to establish the femur defect model according to procedures as previously described. 8 Briefly, each rat was given a general anesthetic through an intravenous administration of chloral hydrate (10%, 5.0–7.5 mL/kg). Then, a 1.5 cm incision was made to expose the genu after shaving and disinfection.…”
Section: Methodsmentioning
confidence: 99%